Applying The Fuzzy Delphi Method In The Development Of A Hadith Terminology Dictionary Application (is-hadis) - Suriani Sudi; Nur Saadah Hamisan @Khair; Rosni Wazir; Phayilah Yama; Farhah Zaidar Ramli; Siti Mursyidah Mohd. Zin; Nor Musliza Mustafa (Human Resource Management Academic Research Society, 2025)
The advancement of technology in today’s educational landscape has witnessed the growing use of Artificial Intelligence (AI) across various learning platforms. This technological integration enhances the learning process by making it more interactive, responsive, and flexible, thereby complementing existing traditional methods. In this context, the Hadith Terminology Dictionary Application (IS-HADIS) was developed to facilitate students in accessing information quickly and effectively without the need to consult bulky printed dictionaries. Students simply type the desired term, and the relevant information is displayed almost instantly. This study was conducted to obtain expert consensus on the essential elements required for the design and development of this application. The Fuzzy Delphi Method was employed using a seven-point Likert scale, involving ten experts from the fields of educational technology, multimedia, and information technology. Data were collected through questionnaires distributed to all participating experts. The findings revealed a high level of agreement among the experts regarding the elements examined, with threshold (d) values less than 0.2, agreement percentages exceeding 75%, and defuzzification values above 0.5—except for one element, namely the application introduction element. Overall, this study successfully designed the Hadith Terminology Dictionary Application (IS-HADIS), which can be effectively utilized by educators in higher learning institutions, mosque and surau instructors, as well as students, as a valuable learning support tool.